Research progress in the management of vascular disease with cannabidiol: a review - Yilong Guo; Ren Wei; Jianqing Deng; Wei Guo (Journal of Cardiothoracic Surgery, 2024)
Abstract The morbidity and mortality rates associated with vascular disease (VD) have been gradually increasing. Currently, the most common treatment for VD is surgery, with the progress in drug therapy remaining slow. Cannabidiol (CBD) is a natural extract of Cannabis sativa L. with sedative, analgesic, and nonaddictive properties. CBD binds to 56 cardiovascular-related receptors and exerts extensive regulatory effects on the cardiovascular system, making it a potential pharmacological agent for the management of VD. However, most CBD studies have focused on neurological and cardiac diseases, and research on the management of VD with CBD is still rare. In this review, we summarize the currently available data on CBD in the management of VD, addressing four aspects: the major molecular targets of CBD in VD management, pharmacokinetic properties, therapeutic effects of CBD on common VDs, and side effects. The findings indicate that CBD has anti-anxiety, anti-oxidation, and anti-inflammatory properties and can inhibit abnormal proliferation and apoptosis of vascular smooth muscle and endothelial cells; these effects suggest CBD as a therapeutic agent for atherosclerosis, stress-induced hypertension, diabetes-related vasculopathy, ischemia-reperfusion injury, and vascular damage caused by smoking and alcohol abuse. This study provides a theoretical basis for further research on CBD in the management of VD.